2009
DOI: 10.1128/iai.01075-08
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Opsonic and Nonopsonic Serotype 3 Pneumococcal Capsular Polysaccharide-Specific Monoclonal Antibodies against Intranasal Challenge withStreptococcus pneumoniaein Mice

Abstract: Serotype-specific antibodies to pneumococcal capsular polysaccharide (PPS) are a critical component of vaccine-mediated immunity to Streptococcus pneumoniae. In this study, we investigated the in vitro opsonophagocytic activities of three PPS-specific mouse immunoglobulin G1 monoclonal antibodies (MAbs), 1E2, 5F6, and 7A9, and determined their in vivo efficacies against intranasal challenge with WU2, a serotype 3 pneumococcal strain, in normal and immunodeficient mice. The MAbs had different in vitro activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
118
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(121 citation statements)
references
References 87 publications
2
118
0
1
Order By: Relevance
“…Murine Fc␥RI binds IgG2a; Fc␥RIIB binds IgG1, IgG2a, and IgG2b; Fc␥RIII binds IgG1, IgG2a, and IgG2b; and Fc␥RIV binds IgG2a and IgG2b (33). In a previous study, Tian et al reported that PPS3-specific mouse IgG1 MAbs that do (7A9 and 5F6) and do not (1E2) promote phagocyte-mediated opsonophagocytic killing of ST3 in vitro were each able to protect wild-type C57BL/6 (Wt) mice against lethal intranasal infection with ST3 (49). The MAbs that promoted in vitro killing (7A9 and 5F6) required Fc␥RIIB and neutrophils to mediate protection, whereas the one that did not (1E2) required the FcR common gamma chain (Fc␥R) but not Fc␥RIIB or neutrophils (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Murine Fc␥RI binds IgG2a; Fc␥RIIB binds IgG1, IgG2a, and IgG2b; Fc␥RIII binds IgG1, IgG2a, and IgG2b; and Fc␥RIV binds IgG2a and IgG2b (33). In a previous study, Tian et al reported that PPS3-specific mouse IgG1 MAbs that do (7A9 and 5F6) and do not (1E2) promote phagocyte-mediated opsonophagocytic killing of ST3 in vitro were each able to protect wild-type C57BL/6 (Wt) mice against lethal intranasal infection with ST3 (49). The MAbs that promoted in vitro killing (7A9 and 5F6) required Fc␥RIIB and neutrophils to mediate protection, whereas the one that did not (1E2) required the FcR common gamma chain (Fc␥R) but not Fc␥RIIB or neutrophils (49).…”
mentioning
confidence: 99%
“…However, ST-specific antibodies that mediate protection against pneumococcus in mouse models, but do not promote opsonophagocytic killing in vitro (9,10,18,49), have been identified. Such antibodies include PPS3-specific human and mouse monoclonal antibodies (MAbs) that protect mice against lethal pneumonia and sepsis with ST3 (49). Understanding the mechanism(s) by which antibodies to PPS3 mediate protection is important.…”
mentioning
confidence: 99%
“…Given the discrete gene use of the PPS-and PC-specific MAbs reported herein and the observation that only PPS-specific MAbs were protective, analysis of the gene use of PPS-binding B cells could have the potential to reveal PPS specificity and possibly to predict function. Although certain PPS determinants might elicit antibodies that are less protective than others, the molecular signatures of such antibodies could also be discrete, as described for PPS3-binding MAbs (14,52). Hence, antibody structure-function relationships could hold promise as biomarkers and/or as a component of a new generation of surrogates for pneumococcal vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For infection, mice were given 50, 100, or 1,000 CFU of ST8 (6308) or 100 or 200 CFU of ST3 (WU2). This infection model is based on the historical serum potency assay (8) and has been used previously to study the efficacy of MAbs to PPS in vivo (14,43,52,55).…”
mentioning
confidence: 99%
See 1 more Smart Citation